An Evaluation of Language Learning, Sentence Construction and Writing Developed for Third Graders with Hearing Impairment - Ahmad Ramezani; Abdossaeid Mohammadshafiei; Zeinab Yazdani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The current study deals with the face and content analysis of the Language Learning, Sentence Construction and Writing Textbook, developed for the third grade. It is a descriptive-analytic research study, using both qualitative (including focus group and content analysis) and quantitative methods. For the qualitative process, a targeted sampling technique was applied, and the data were gathered through semi-constructed interviews. Some strengths of the textbook were the good title, no racial/ethnic and gender biases, and attention to students’ favorite activities. However, the lack of appropriate content list, too heavy content, disregarding language competence or the ability of students with hearing impairment were among the weaknesses. Using the census method for the quantitative assessment, the statistical population consisted of teachers of third-grade hearing-impaired from Isfahan province (n=35). The quantitative findings revealed that the correlation between the scores of the two characteristics mentioned was 0.85 (p<0.01). The t-test value obtained for the two correlated sets of scores was not significant at the 0.05 level (t=0.103, df=33). To put it differently, there is no difference in the average teachers’ evaluation scores for content and face analysis of the Language Learning, Sentence Construction and Writing textbook.